Scatter-hoarding in Acomys subspinosus : the roles of seed traits, seasonality and cache retrieval - Rusch, Ursina Denise (Stellenbosch : Stellenbosch University, 2011)
Thesis (MSc)--Stellenbosch University, 2011.